2010
DOI: 10.5005/jcdp-11-5-25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Load Cycling on the Microleakage of Beveled and Nonbeveled Margins in Class V Resin-Based Composite Restorations

Abstract: Aim: This study evaluated the influence of mechanical loading and thermocycling on microleakage of class V resin-based composite restorations with and without enamel bevel. Methods and Materials: Sixty class V cavity preparations measuring 3.0 mm wide (mesiogingivally) x 2.0 mm high (occluso-gingivally) x 1.5 mm deep with the occlusal margin in enamel and the gingival margin in cementum were prepared on the buccal surfaces of human premolars using a #12 diamond round bur (Drendel & Zweiling Diamant GmbH, Lemgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…This was in accordance with Kubo et al 67 and Swathi et al, 68 who stated that nanoleakage of composite restorations occurs because of stress placed along the tooth–restoration interface due to various factors, such as polymerization shrinkage, thermo-cycling in the oral environment, and mechanical fatigue through repetitive masticatory loading. Also, our findings are in agreement with Ameri et al 38 and Bedran-de-Castro et al, 43 who concluded that cyclic loading increased nanoleakage of the margins of Class V composite restorations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This was in accordance with Kubo et al 67 and Swathi et al, 68 who stated that nanoleakage of composite restorations occurs because of stress placed along the tooth–restoration interface due to various factors, such as polymerization shrinkage, thermo-cycling in the oral environment, and mechanical fatigue through repetitive masticatory loading. Also, our findings are in agreement with Ameri et al 38 and Bedran-de-Castro et al, 43 who concluded that cyclic loading increased nanoleakage of the margins of Class V composite restorations.…”
Section: Discussionsupporting
confidence: 93%
“…The diversities in the reported data could be attributed to dissimilarities between preparation types and sizes; operator variability; materials used; and load cycle values, direction, and number. 38 , 70 On the other hand, a limitation of this study is that it was carried out in laboratory conditions, negating the effect of pulpal pressure on the used restorative systems. Thus, more clinical evaluations should be carried out as such in vitro studies do not eliminate the need for clinical ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A round carbide bur size # 023 * with high speed hand piece was used under water coolant. The depth of the cavity was adjusted to 2 mm by inserting the entire head of the bur (14) .…”
Section: Cavity Preparationmentioning
confidence: 99%
“…favorecer a sua longevidade, por conseguinte (Ichim et al, 2007a;Tyas, 2012;Soares et al, 2013). Nesse caso, quando as cavidades passam a ter forma de U, é que maiores tensões se concentram na margem gengival, em comparação à oclusal (Ameri et al, 2010).…”
Section: Cunhaunclassified